Management of symptoms in patients with advanced chronic heart failure (Paliativní medicína, 2022)
Shortness of breath is one of the basic symptoms of heart failure. Renin-angiotensin blockers,beta-blockers, mineralocorticoid receptor antagonists and sodium-glucose cotransporter2 inhibitors currently form the basis for the treatment of dyspnoea in heart failure with reducedejection fraction. Empagliflozin is newly used in the treatment of heart failure with preservedejection fraction. Symptomatic treatment is based mainly on diuretics, parenteral iron substitution,in specific cases digoxin or inotropics are used. Opioids are used in the treatment of refractorydyspnea. Instrumental treatment also plays an important role, in the first place cardiacresynchronization, and mechanical cardiac support in indicated patients. Oxygen therapyis indicated in patients with hypoxemia. The use of individual procedures in a particular patientchanges with the development of the disease and the change in the goals of care.
Keywords: dyspnea, chronic heart failure, palliative care